Effect of moringa seed extract in chlorpyrifos-induced cerebral and ocular toxicity in mice - Alanazi, Ibtesam S.; Altyar, Ahmed E.; Zaazouee, Mohamed Sayed; Elshanbary, Alaa Ahmed; Abdel-Fattah, Abdel-Fattah M.; Kamel, Mohamed; Albaik, Mai; Ghaboura, Nehmat (Frontiers in Veterinary Science, 2024)
Chlorpyrifos (CPF) is one of the most commonly used organophosphosphate-based (OP) insecticides. Its wide use has led to higher morbidity and mortality, especially in developing countries. Moringa seed extracts (MSE) have shown neuroprotective activity, antioxidant, anti-inflammatory, and antibacterial features. The literature lacks data investigating the role of MSE against CPF-induced cerebral and ocular toxicity in mice. Therefore, we aim to investigate this concern. A total of 40 mature male Wistar Albino mice were randomly distributed to five groups. Initially, they underwent a one-week adaptation period, followed by a one-week treatment regimen. The groups included a control group that received saline, MSE 100 mg/kg, CPF 12 mg/kg, CPF-MSE 50 mg/kg, and CPF-MSE 100 mg/kg. After the treatment phase, analyses were conducted on serum, ocular, and cerebral tissues. MSE100 and CPF-MSE100 normalized the pro-inflammatory markers (interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α)) and AChE serum levels. CPF-MSE50 significantly enhanced these serum levels compared to CPF; however, it showed higher levels compared to the control. Moreover, the tissue analysis showed a significant decrease in oxidative stress (malondialdehyde (MDA) and nitric oxide (NO)) and an increase in antioxidant markers (glutathione (GSH), glutathione peroxidase (GSH-PX)), superoxide dismutase (SOD), and catalase (CAT) in the treated groups compared to CPF. Importantly, the significance of these effects was found to be dose-dependent, particularly evident in the CPF-MSE100 group. We conclude that MSE has a promising therapeutic effect in the cerebral and ocular tissues of CPF-intoxicated mice, providing a potential solution for OP public health issues.